Wild Australian birds and drug-resistant bacteria: characterisation of antibiotic-resistant Escherichia coli and Enterococcus spp. (2nd October 2019) - Smith, Hannah G.; Clarke, Rohan H.; Larkins, Jo-Ann; Bean, David C.; Greenhill, Andrew R.
ABSTRACT: Birds can spread microorganisms through their movement; however, it is still not fully understood how wild birds acquire and disperse antimicrobial-resistant (AMR) bacteria. We sampled wild Australian birds from three geographically distinct locations for the presence of AMR strains of two clinically important species of bacteria, Escherichia coli and Enterococcus spp. A total of 121 birds were sampled, representing 15 different species. Thirty E. coli and 54 Enterococcus isolates were tested for resistance to 12 and 8 different antibiotics, respectively. Resistance to at least one antibiotic was common, being detected in 96% of Enterococcus and 60% of E. coli isolates. The vancomycin-resistance genes vanA and vanD were detected in 22% of enterococci (13% vanA, 9% vanD ), while 9% displayed phenotypic resistance with no associated gene. Wild birds are a carrier of AMR bacteria in Australia, and are capable of harbouring a more diverse range of vancomycin-resistance genes than is typically seen among Australian clinical isolates.